2018
DOI: 10.1186/s10152-018-0517-3
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the settlement of non-indigenous species in benthic communities from an oceanic island

Abstract: The introduction of non-indigenous species (NIS) in new environments represents a major threat for coastal ecosystems. A good understanding of the mechanisms and magnitude of the impact of NIS colonisation on native ecosystems is becoming increasingly crucial to develop mitigation measures and prevent new invasions. In this present study, we asked if distinct coastal benthic communities from an oceanic island can have different vulnerability to NIS colonisation process. First, PVC settlement plates were deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…The high invasion success has been reported in disturbed ecosystems and communities with low species diversity because these disturbed habitats have high and frequent inputs of invasive non-natives in harbours and marinas. This integration increases the invasion success, and thus the colonization risk increases in the established communitie (Riera et al, 2018). In contrast, in polluted marine habitats, propagule pressure restricts invasive non-native settlement compared to other parameters such as abiotic factors (pollutants) or environmental disturbance, so it is interesting to note that under natural conditions, these disturbed habitats and propagule pressures are often related to each other in terms of invasive non-native diversity (Riera et al, 2018).…”
Section: How Is the Invasive Non-native Species Diversity Affected By...mentioning
confidence: 99%
“…The high invasion success has been reported in disturbed ecosystems and communities with low species diversity because these disturbed habitats have high and frequent inputs of invasive non-natives in harbours and marinas. This integration increases the invasion success, and thus the colonization risk increases in the established communitie (Riera et al, 2018). In contrast, in polluted marine habitats, propagule pressure restricts invasive non-native settlement compared to other parameters such as abiotic factors (pollutants) or environmental disturbance, so it is interesting to note that under natural conditions, these disturbed habitats and propagule pressures are often related to each other in terms of invasive non-native diversity (Riera et al, 2018).…”
Section: How Is the Invasive Non-native Species Diversity Affected By...mentioning
confidence: 99%
“…In such cases, native consumers (predators and grazers) often reject feeding on NIS and selectively target a native-based diet. This behaviour can facilitate the proliferation and spread of NIS [20][21][22][23]. In contrast, local consumers that feed on NIS can control NIS dominance through trophic interactions, exerting a top-down control over potential invaders [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also indicated that the invasive species have a competitive edge over the native species as they have relatively high reproductive rate, high survival rate, fast growth and phenotypic plasticity (Dafforn 2017;Simpson et al 2017;Epstein & Smale 2018;Riera et al 2018). Ultimately, non-native species may perform better at an invaded area than at their native regions (e.g., Parker et al 2013).…”
Section: Impacts Of Man-made Structures On Bioinvasionsmentioning
confidence: 99%
“…With the proliferation of man-made structures along the world's coast, there are many chances for a non-native species to establish and spread (Simberloff & Von Holle 1999;Bulleri et al 2006;Tyrrell & Byers 2007;Dafforn et al 2009Dafforn et al , 2012Airoldi & Bulleri 2011;Perkol-Finkel et al 2012;Theuerkauf et al 2018). This is especially the case for Northern hemisphere M. galloprovincialis, which is known as one of the aggressive invaders, with competitive traits such as high growth, high reproduction rate and phenotypic plasticity that help them acclimatise to many environments (Dafforn 2017;Simpson et al 2017;Epstein & Smale 2018;Riera et al 2018). Having said that, M. galloprovincialis is highly used in shellfish industries for its economic value all around the world as it has successfully invaded most of the regions worldwide (Wonham 1999;Daguin & Borsa, 2000;Hilbish et al 2000;Anderson & Thompson 2002;Borsa et al 2012;Oyarzún et al 2016;Pickett & David 2018).…”
Section: Shell Lengthmentioning
confidence: 99%
See 1 more Smart Citation